An Analysis of the Seven Elements of Universal Culture in the Kampung Naga Community as a Resource for Social Studies Learning Based on Local Wisdom - Dena Mustika; Sari Sri Handani; Saeful Gunawan (Lembaga Bale Literasi, 2025)
This study aims to examine seven elements of universal culture that have developed within the community of Kampung Naga and to explore their use as a resource for social studies education based on local wisdom. This study employs a qualitative approach using a descriptive qualitative method. Data were collected through field observations, interviews with local residents, literature reviews, and document analysis, and were subsequently analyzed through the stages of data collection, reduction, presentation, and drawing conclusions. The research findings indicate that the seven elements of universal culture namely, religious systems, social organization, knowledge, livelihoods, technology and tools of daily life, language, and the arts are still preserved and practiced in the daily lives of the Kampung Naga community. Furthermore, the study’s findings indicate that the cultural values and practices of the Kampung Naga community can serve as a source of social studies learning across various topics, such as social life, economic activities, cultural diversity, human-environment interactions, and cultural change and sustainability. Thus, Kampung Naga can serve as a rich source of social studies learning, capable of supporting meaningful learning and contributing to the strengthening of students’ character and cultural awareness.